An EJC Factor RBM8a Regulates Anxiety Behaviors - Alachkar, A.; Jiang, D.; Harrison, M.; Zhou, Y.; Chen, G.; Mao, Y. (Current Molecular Medicine, 2013)
Neuroplasticity depends on the precise timing of gene expression, which requires accurate control of mRNA stability and rapid elimination of abnormal mRNA. Nonsense-mediated mRNA decay (NMD) is an RNA surveillance mechanism that ensures the speedy degradation of mRNAs carrying premature termination codons (PTCs). This mechanism relies on several key Exon Junction Complex (EJC) factors to distinguish PTCs from normal stop codons. NMD degrades not only aberrant transcripts carrying PTCs, but also normal transcripts harboring a normal stop codon [1]. Intriguingly, mutations in an NMD factor, Upf3b, have been found in patients with autism [2, 3]. A binding partner of Upf3b, RBM8a, is located in the 1q21.1 copy-number variation (CNV) associated with mental retardation, autism [4], schizophrenia [5], and microcephaly [6]. However, the functions of EJC factors and their roles in behavioral regulation are still elusive. RBM8a protein is a core component of the EJC that plays an important role in NMD. Recent genetic study indicated that RBM8a gain-of-function significantly associated with intellectual disability [7]. In this study we investigated the effect of RBM8a overexpression on affective behaviors in mice. Lentivirus expressing RBM8a was infused into the hippocampus of adult mice to conduct behavioral studies including social interaction, open field, elevated plus maze, and forced swimming tests. Our results showed that overexpression of RBM8a in the mouse dentate gyrus (DG) leads to increased anxiety-like behavior, abnormal social interaction and decreased immobile time in forced swimming test (FST). To examine the underlying mechanism, we found that overexpressing RBM8a in cultured primary neurons lead to significant higher frequency of miniature excitatory postsynaptic currents (mEPSCs). To explore the underlying mechanism of RBM8a mediated behavioral changes, RNAimmunoprecipitation (RNA-IP) detected that RBM8a binds to CaMK2, GluR1 and Egr1 mRNA, suggesting that RBM8a may target neuronal genes to regulate behaviors. This is the first study that demonstrates the key role of RBM8a on the emotional behaviors in mice. These results reveal new neural mechanisms by which NMD modulates behaviors and potentially provide a better understanding of pathophysiology underlying psychiatric disorders.
Keywords: Adult neurogenesis